NALISIS TOKOH DAN PENOKOHAN SERTA NILAI-NILAI PENDIDIKAN RELIGIUS PADA NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - Febriasari, Diani (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2017)
ABSTRACT In this global era, Indonesia society are facing a crisis of values and character. It's seen from increasing cases of rape, fights, rustling, drugs, alcohols, conflict of inter-religious, ethnics, racial, etc. The complexity of this problem must be balanced with incessant instill of religious values. Based on the background of the problems above, the purpose of this study was to know the figures and characterization analysis and also presentation forms of religious education values in novel